Educational research and innovation from Master´s Classroom in Social Studies Teacher Training to curricular practices in Secondary Education´s Classroom - Laura Triviño Cabrera; Cristian Requena Palacios (Universidad de La Rioja, 2019)
This article tries to explain how professor-academic tutor and trainee student from Master in Secondary Teacher Training, specialize in Social Sciences, of the Málaga University, developped in parallel projects-based learning. The aim of the projects was the audiovisual co-education of students of that master and students at the Huerta Alta High School. While professor-academic tutor was applying an educational research design on Media and Information Literacy in two subjects (Design and development of lessons and classroom activities and History, Geography and Philosophy Curriculum); the trainee student was applying a similar educational research design in the subject: Social Changes and Gender. The results of these projects were the creation of audiovisual productions. Students of the master made videoclips and students of the high school made a short film. All audiovisual productions were introduced by students in Clara Peeters Seminar: Audiovisual Empowerment!